2000
DOI: 10.1590/s0001-37652000000100013
|View full text |Cite
|
Sign up to set email alerts
|

Entry, dispersion and differentiation of microglia in the developing central nervous system

Abstract: Microglial cells within the developing central nervous system (CNS) originate from mesodermic precursors of hematopoietic lineage that enter the nervous parenchyma from the meninges, ventricular space and/or blood stream. Once in the nervous parenchyma, microglial cells increase in number and disperse throughout the CNS; these cells finally differentiate to become fully ramified microglial cells. In this article we review present knowledge on these phases of microglial development and the factors that probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 86 publications
3
53
0
1
Order By: Relevance
“…This supports the view that Mü ller cells are the substratum for radial migration of microglial cells in the avian retina, as previously suggested Navascués et al, 2000Navascués et al, , 2002. This is not surprising, because Mü ller cells are radially oriented retinal components.…”
Section: Radially Migrating Microglial Cells Adhere To Mü Ller Cell Rsupporting
confidence: 90%
See 1 more Smart Citation
“…This supports the view that Mü ller cells are the substratum for radial migration of microglial cells in the avian retina, as previously suggested Navascués et al, 2000Navascués et al, , 2002. This is not surprising, because Mü ller cells are radially oriented retinal components.…”
Section: Radially Migrating Microglial Cells Adhere To Mü Ller Cell Rsupporting
confidence: 90%
“…Therefore, in situ studies of the central nervous system (CNS) are necessary to understand the cellular mechanisms of microglial migration. Studies of this type in the developing CNS revealed that microglial cells use tangential and radial migration to go from their entry points into the CNS to their final destinations (Navascués et al, 2000(Navascués et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The primitive microglial cells have a large cell body bral hemispheres from early neurogenesis and tend to increase in number during CNS differentiation. These observations corroborate the hypothesis presented by others (10) and are compatible with the descriptions of different areas of the CNS including the quail cerebellum (26), quail retina (22) and the prenatal rat hippocampus (27). Microglia constitute a significant part of the glial cell population, between 5 and 12% of the total number of CNS cells (28), and are distributed unevenly in the regions of the CNS (29,30).…”
Section: Discussionsupporting
confidence: 91%
“…In 16-day-old embryos the differentiation of neurons is sufficiently advanced to enable the distinction between neurons and glial cells by tritiated thymidine autoradiography (5,6). The neurons, astrocytes and oligodendrocytes arise from the neuroectoderm (7); however, the origin of microglial cells is still controversial (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation